Consumer Protection in Social Media-Based Digital MSME Transactions: Sharia Perspective: Perlindungan Konsumen Dalam Transaksi Umkm Digital Berbasis Media Sosial : Perspektif Syaria’h - Andi Rahmad Hidayar; Ach. Rosidi (JEIZA : Jurnal Ekonomi Islam Az-Zain, 2025)
The rapid expansion of social media platforms such as TikTok, Instagram, and Shopee has created significant opportunities for Micro, Small, and Medium Enterprises (MSMEs) to broaden their market reach, lower promotional costs, and engage directly with consumers. However, these advantages are accompanied by notable consumer protection challenges, including insufficient product information disclosure, the absence of return policies, and weak after-sales services. This study therefore aims to analyze consumer protection practices among social media-based digital MSMEs and evaluate them from a sharia economic perspective. A qualitative descriptive approach was employed, with data collected through observations, in-depth interviews with MSME actors and consumers, and an extensive literature review. The data were analyzed by linking field findings with Law Number 8 of 1999 on Consumer Protection and core sharia principles such as ʿadl (justice), ṣidq (honesty), bayyinah (openness), al-khiyār (the right to choose), and iḥsān (good service). The results indicate that around 65% of MSME actors fail to provide complete product information, most lack transparent return policies, and complaint-handling mechanisms remain weak. Such practices lead to gharar (ambiguity) and tadlis (fraud), contradicting both sharia principles and positive law. The study recommends enhancing legal and sharia literacy, implementing transparent return policies, and adopting technology that promotes halal and fair trade to strengthen consumer trust and ensure business sustainability.